COMPARISON OF FUNCTIONAL OUTCOMES BETWEEN CEMENTED AND UNCEMENTED TOTAL HIP ARTHROPLASTY IN ELDERLY PATIENTS - Dr. Abhishek; Dr. Rahul Bains, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Total hip arthroplasty (THA) is a common intervention in elderly patients with hip pathology. The optimal fixation method—cemented or uncemented—remains debated, especially concerning functional outcomes and complication rates. Aim: To compare the functional outcomes of cemented versus uncemented total hip arthroplasty in elderly patients. Methods: This prospective observational study included 120 patients aged ≥60 years undergoing primary THA. Patients were divided into cemented (n=62) and uncemented (n=58) groups. Baseline demographics, diagnosis, and preoperative Harris Hip Scores (HHS) were recorded. Functional outcomes were assessed at 12 months postoperatively using HHS, Visual Analog Scale (VAS) for pain, walking distance, and walking aid usage. Postoperative complications and radiological outcomes including implant stability and subsidence were also evaluated. Statistical analysis involved t-tests and chi-square tests, with significance set at p<0.05. Results: Both groups were comparable at baseline. At 12 months, the cemented group had significantly higher mean HHS (86.5 ± 7.8 vs. 82.9 ± 8.5, p=0.011) and lower VAS pain scores (1.8 ± 1.1 vs. 2.3 ± 1.3, p=0.035). Walking distance and walking aid use favored cemented THA but were not statistically significant. Periprosthetic fractures were significantly less frequent in the cemented group (3.2% vs. 12.1%, p=0.049). Radiologically, implant stability was comparable, but subsidence was significantly less in cemented implants (0.8 ± 0.4 mm vs. 1.3 ± 0.7 mm, p<0.001). Conclusion: Cemented THA offers superior early functional outcomes and better implant stability with fewer periprosthetic fractures in elderly patients compared to uncemented THA. Cemented fixation should be preferred in this population to optimize postoperative recovery.